How to improve the outcomes of elderly acute myeloid leukemia patients through allogeneic hematopoietic stem cell transplantation - Jiang, Shan; Yan, Han; Lu, Xuan; Wei, Ruowen; Chen, Haoran; Zhang, Ao; Shi, Wei; Xia, Linghui (Frontiers in Immunology, 2023)
In recent years, with the gradual advancement of haploidentical transplantation technology, the availability of donors has increased significantly, along with the widespread use of reduced-intensity conditioning and the improvement of nursing techniques, giving more elderly acute myeloid leukemia (AML) patients the chance to receive allogeneic hematopoietic stem cell transplantation. We have summarized the classic and recently proposed pre-transplant assessment methods and assessed the various sources of donors, conditioning regimens, and post-transplant complication management based on the outcomes of large-scale clinical studies for elderly AML patients.